Análisis de contenido del medio digital el Cardenal EC y diario El Correo en Facebook: caso segunda vuelta electoral 2025 entre Daniel Noboa y Luisa González - Matailo Pauta, Cristina Elizabeth; Sisalima Corte, Jessica Estefania (Machala : Universidad Técnica de Machala, 2025)
This research analyzes the political content disseminated on Facebook by two digital media outlets from the city of Machala, El Oro province, Ecuador: El Cardenal EC and El Diario Correo, during the second round of the April 2025 presidential elections, in which Daniel Noboa and Luisa González competed. The general objective was to analyze the political content published by both outlets during this electoral process, while the specific objectives were to determine the content issued about each candidate and to identify the journalistic narratives employed. The methodology followed a mixed approach, combining qualitative and quantitative techniques through content analysis of posts published between April 1 and April 12, 2025, along with semi-structured interviews with experts in communication and local journalism. The study population comprised all publications from both outlets during that period, applying non-probabilistic criterion sampling to select only those posts that directly or indirectly mentioned the candidates. The analysis matrix was adapted from the thesis by Landacay Santos and Salinas Armijos (2023) on social media and politics in El Oro province, incorporating variables such as content type, journalistic narrative, message tone, and level of interaction. The results showed that El Cardenal EC acted as the dominant promotional vehicle for Daniel Noboa, with three-quarters of its content displaying a positive tone toward his candidacy, while approximately one-fifth of its publications took a negative stance toward Luisa González, mainly through flyers and sponsored videos. In contrast, El Diario Correo presented a more balanced volume of posts about both candidates; however, it maintained a critical bias toward Luisa González, using opinion pieces, caricatures, ideological comparisons, and mocking posts that questioned her candidacy, while publications about Daniel Noboa focused on his political management, security, and economic proposals. Overall, the tone revealed high positivity (82%) toward Noboa, favored by institutional and advertising coverage, while González accumulated two-thirds negative tone, mainly associated with allegations and criticism. The predominant journalistic narratives in El Cardenal EC were descriptive-informative and persuasive, whereas in El Diario Correo they were opinion-based, mocking, and ideological analysis, with few posts maintaining a strictly institutional tone. The semi-structured interviews reflected experts’ perceptions of the lack of balance and transparency in local digital media during electoral processes, as well as the need to strengthen journalistic ethics to ensure objective information for citizens and contribute to democracy. The study concludes that the digital coverage of both outlets demonstrated narrative and tonal imbalances, creating a communication ecosystem that favors the reproduction of polarized discourses and asymmetries in access to balanced information. This research contributes to understanding the role of local digital media in contemporary political communication, enabling reflection on their impact on public opinion and democracy in contexts of high electoral tension in Ecuador.
La presente investigación analiza el contenido político difundido en Facebook por dos medios digitales de la ciudad de Machala de la red social Facebook, provincia de El Oro, Ecuador: El Cardenal EC y El Diario Correo, durante la segunda vuelta presidencial de abril de 2025, en la que se enfrentaron Daniel Noboa y Luisa González. El objetivo general fue analizar el contenido político emitido por ambos medios en dicho proceso electoral, mientras que los objetivos específicos consistieron en determinar los contenidos emitidos sobre cada candidato e identificar las narrativas periodísticas utilizadas. La metodología empleada fue de enfoque mixto, combinando técnicas cualitativas y cuantitativas mediante el análisis de contenido de publicaciones realizadas entre el 1 hasta el 12 de abril de 2025, y entrevistas semiestructuradas a expertos en comunicación y periodismo local. La población estuvo conformada por todas las publicaciones de ambos medios en ese periodo, aplicándose un muestreo no probabilístico por criterio para seleccionar únicamente aquellas publicaciones que mencionaran directa o indirectamente a los candidatos. La matriz de análisis se adaptó de la tesis de Landacay Santos y Salinas Armijos (2023) sobre redes sociales y política en la provincia de El Oro, incorporando variables como tipo de contenido, narrativa periodística, tono del mensaje y nivel de interacción. Los resultados evidenciaron que El Cardenal EC actuó como vehículo promocional dominante para Daniel Noboa, con tres cuartas partes de su contenido en tono positivo hacia su candidatura, mientras que aproximadamente una quinta parte de sus publicaciones tuvo un enfoque negativo hacia Luisa González, principalmente mediante flyers y videos patrocinados. En contraste, El Diario Correo presentó un volumen más equilibrado de publicaciones sobre ambos candidatos; sin embargo, mantuvo un sesgo crítico hacia Luisa González, utilizando notas de opinión, caricaturas, comparaciones ideológicas y publicaciones en tono de burla que cuestionaban su candidatura, mientras que las publicaciones sobre Daniel Noboa se centraron en su gestión política, seguridad y propuestas económicas. El tono global evidenció una alta positividad (82%) hacia Noboa, favorecido por coberturas institucionales y publicitarias, mientras que González acumuló dos tercios de tono negativo, asociado principalmente a denuncias y críticas. Asimismo, las narrativas periodísticas predominantes fueron de tipo descriptivo-informativo y persuasivo en El Cardenal EC, mientras que en El Diario Correo fueron de opinión, burla y análisis ideológico, destacando que pocos posts mantuvieron un tono estrictamente institucional. Las entrevistas semiestructuradas revelaron la percepción de expertos sobre la falta de equilibrio y transparencia en los medios digitales locales durante procesos electorales, así como la necesidad de fortalecer la ética periodística para garantizar información objetiva a la ciudadanía y aportar a la democracia. La investigación concluye que la cobertura digital de ambos medios evidenció desequilibrios narrativos y de tono, configurando un ecosistema comunicacional que favorece la reproducción de discursos polarizados y asimetrías en el acceso a información equilibrada. Este estudio aporta a la comprensión del rol de los medios digitales locales en la comunicación política contemporánea, permitiendo reflexionar sobre su impacto en la opinión pública y la democracia en contextos de alta tensión electoral en Ecuador.
Keywords: ANÁLISIS DE CONTENIDO; NARRATIVAS PERIODÍSTICAS; FACEBOOK; ELECCIONES ECUADOR